2006
DOI: 10.1051/0004-6361:20053844
|View full text |Cite
|
Sign up to set email alerts
|

H I observations of galaxies

Abstract: High sensitivity 21-cm H i line observations with an rms noise level of ∼0.5 mJy were made of 35 spiral galaxies in the Coma Supercluster, using the refurbished Arecibo telescope, leading to detection of 25 objects. These data, combined with the measurements available in the literature, provide the set of H i data for 94% of all late-type galaxies in the Coma Supercluster with an apparent photographic magnitude m p ≤ 15.7 mag. We confirm that the typical scale of H i deficiency around the Coma cluster is 2 Mpc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
92
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 72 publications
(103 citation statements)
references
References 42 publications
10
92
1
Order By: Relevance
“…In this figure, we include all galaxies which have H I mass larger than 10 4 h −1 M . The magenta arrow represents the lower limit of the overall H I mass of the Coma cluster by summing H I masses of 223 H I-detected late-type galaxies in Gavazzi et al (2006). The total mass of the Coma cluster from Kubo et al (2007) is shown for comparison.…”
Section: Imprinted Photoionization Feedback On H I Clusteringmentioning
confidence: 99%
“…In this figure, we include all galaxies which have H I mass larger than 10 4 h −1 M . The magenta arrow represents the lower limit of the overall H I mass of the Coma cluster by summing H I masses of 223 H I-detected late-type galaxies in Gavazzi et al (2006). The total mass of the Coma cluster from Kubo et al (2007) is shown for comparison.…”
Section: Imprinted Photoionization Feedback On H I Clusteringmentioning
confidence: 99%
“…It has also become clear that the physical properties of star-forming systems that inhabit rich environments, which are characterised by a reduced atomic (e.g. Cayatte et al 1990;Solanes et al 2001;Vollmer et al 2001;Gavazzi et al 2006a) and molecular gas content (Fumagalli et al 2009;Boselli et al 2014c), dust content 2012a), and star formation (e.g. Gavazzi et al 1998Gavazzi et al , 2006bGavazzi et al , 2013Lewis et al 2002;Goto et al 2003;Boselli et al 2015), are systematically different from those of their isolated analogues.…”
Section: Introductionmentioning
confidence: 99%
“…Tully & Shaya 1984;Colless & Dunn 1996) whose physical properties systematically change once they reach the densest regions. It is now widely recognised that late-type galaxies located in rich clusters are generally HI-deficient Gavazzi 1987;Cayatte et al 1990;Solanes et al 2001;Gavazzi et al 2005Gavazzi et al , 2006a. There is growing evidence indicating that they also lack molecular gas (Fumagalli et al 2009;Boselli et al 2014b) and dust (Cortese et al 2012a) with respect to similar Visiting astronomer at CSIRO Astronomy and Space Science, Australia Telescope National Facility, PO Box 76, Epping, NSW 1710, Australia. objects in the field.…”
Section: Introductionmentioning
confidence: 99%